Game theory based autonomous vehicles operation. (1st January 2014) - Kim, Changwon; Langari, Reza
In this paper, we propose a game theory based approach to decision making with application to the operation of autonomous ground vehicles in highway setting. The mixed-motive game theory is utilised as a decisionmaking strategy in the context of a two-player game involving autonomous vehicles. The payoff matrices are defined by considering the safety of each player's decision combination in view of their desire to stay within a given lane or to change lanes in consideration of the traffic conditions that the vehicles encounter. By analysing the payoff matrix, either a pure (deterministic) strategy or a mixed (probabilistic) strategy is selected. Three 10 km velocity profiles are predefined for simulation purposes. The simulation results demonstrate effective driving performance. In particular when it is compared with non-game theory cases, game theory based results show larger payoff for both vehicles and smaller payoff differences, securing safe manoeuvring via lane change manoeuvre (LCM) and adaptive cruise control (ACC).